Comparison of Enamel Demineralisation Scores between Passive Self-Ligation Brackets and Conventional Ligation Brackets in Patients Undergoing Orthodontic TreatmentA Laser Fluorescence Study - Akriti Tiwari; Ravindra Kumar Jain (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Enamel demineralisation is often seen in patients undergoing fixed orthodontic treatment because appliances create retentive areas around the brackets leading to food debris accumulation. The method of ligation is also an additional factor in causing plaque accumulation leading to demineralisation around the brackets. Aim: The present study aims to compare enamel demineralisation around self-ligation brackets and conventional ligation brackets at the 3rd month and 12th month of orthodontic treatment using laser fluorescence. Materials and Methods: The present prospective study aims to compare enamel demineralisation around self-ligation brackets (Damon 3mx) and conventional ligation brackets (Gemini 3M) at the 3rd month and 12th month of orthodontic treatment using laser fluorescence. Nineteen subjects who were scheduled for fixed orthodontic treatment were selected for the study and were divided into two groups that is conventional ligation and passive self-ligation. Diagnodent (DD) was used to take enamel demineralisation scores at the time of bonding (T0), 3 months (T1) and 12 months (T2) into treatment. All statistical analysis was performed using IBM SPSS version 20. Chi-square test was performed to find the gender association, One-way ANOVA test was carried out to evaluate the difference of DD scores at time period T0, T1 and T2 in self-ligation group and conventional ligation group and Independent t-test was carried out to evaluate the difference of DD scores between self-ligation brackets and conventional ligation at T0, T1 and T2. Results: One-way ANOVA test reported that in conventional ligation groups there was a statistically significant difference in the mean DD scores between T0 and T1, T0 and T2 (p<0.05). Similarly, in the self-ligation group, a statistically significant difference was observed in the mean DD score between T0 and T1, T0 and T2 (p<0.05). Independent t-test to evaluate the difference of mean DD scores between self-ligation brackets and conventional ligation at T2 was found to be statistically non-significant (p>0.05). No gender association was noted. Conclusion: The method of ligation did not influence enamel demineralisation around orthodontic brackets.